The Myth of Political Neutrality - Tim Honig; Susan Hadley (Voices)
This editorial discusses the roles and meaning of the “political” in music therapy journals and publication processes and calls into question the value and expectation of political neutrality. It also outlines the articles included in the March 2024 issue.